2009
DOI: 10.1098/rsbl.2009.0700
|View full text |Cite
|
Sign up to set email alerts
|

Cope's Rule and Romer's theory: patterns of diversity and gigantism in eurypterids and Palaeozoic vertebrates

Abstract: Gigantism is widespread among Palaeozoic arthropods, yet causal mechanisms, particularly the role of (abiotic) environmental factors versus (biotic) competition, remain unknown. The eurypterids (Arthropoda: Chelicerata) include the largest arthropods; gigantic predatory pterygotids (Eurypterina) during the Siluro-Devonian and bizarre sweep-feeding hibbertopterids (Stylonurina) from the Carboniferous to end-Permian. Analysis of family-level originations and extinctions among eurypterids and Palaeozoic vertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 18 publications
2
93
0
Order By: Relevance
“…They have been interpreted as apex predators in shallow water near shore basins [3][4][5]. A study of the chelicera of the pterygotid Acutiramus cummingsi (Pterygotidae), however, concluded that it could at best 'trap, grasp and slice soft-bodied and relatively weak prey' [6].…”
Section: Introductionmentioning
confidence: 99%
“…They have been interpreted as apex predators in shallow water near shore basins [3][4][5]. A study of the chelicera of the pterygotid Acutiramus cummingsi (Pterygotidae), however, concluded that it could at best 'trap, grasp and slice soft-bodied and relatively weak prey' [6].…”
Section: Introductionmentioning
confidence: 99%
“…The second group includes the mid-sized (,1 m long [2,15]) S. acuminata and Erettopterus species, as well as Eurypterus remipes. The chelicerae of S. acuminata are small with no denticles, similar to the typical eurypterid grasping appendages in E. remipes [16].…”
Section: Resultsmentioning
confidence: 99%
“…The first group includes the large (up to 2.5 m long [1,2]) Jaekelopterus and Pterygotus species, and a specimen representing a new genus and species, IVPP-14593. Both J. rhenaniae and P. anglicus have high visual acuity as indicated by low IOA and a large number of lenses (figure 2 and table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Eurypterids form a prominent component of Silurian faunas in the peri-Gondwanan Prague Basin and, together with cephalopods, are the largest known animals of the Silurian (Lamsdell & Braddy 2010). The oldest eurypterids previously described from the Prague Basin originate from the Ludlow cephalopod limestones, and the acme of the group starts in the lowermost Přídolí but they remain common until the upper Lochkovian.…”
mentioning
confidence: 99%
“…Pterygotids have also been recorded from other peri-Gondwanan basins such as Catalonia, Iberia (Chlupáč et al 1997) and Sardinia (Gnoli 1992, Corradini et al 2009). Increasing abundance of eurypterids throughout the Silurian is a feature shared between the periGondwanan and perhaps even the global marine faunas (Lamsdell & Braddy 2010).…”
mentioning
confidence: 99%